BENTUK DAN MAKNA SIMBOL TARI TEMBUT-TEMBUT DALAM UPACARA ADAT NDILO WARI UDAN PADA MASYARAKAT KARO - dina mariana siregar (Universitas Negeri Medan, 2014)
This study aimed to describe the shape and meaning of symbols Dance Tembut-Tembut in Wari Udan Ndilo Ceremony At The Village People Seberaya Karo Karo District of Tigapanah main focus of this study is to describe the meaning of Form and Meaning of symbols contained in the dance tembut - tembut on Karo society.This study is a description is to collect data and qualitative information, to explain in detail the meaning of Form and Meaning of the symbols of dance Tembut-Tembut, to collect field data methods, interviews, and field observations. The data obtained in the analysis of qualitative tersebutakan. The process of data analysis in this study began with all the data that was obtained from observations and interviews. This study uses the theory of Function, Form and Meaning of symbols, Tembut-tembut dance in ceremonies held at the village uda ndilo wari Seberaya kecanatan Tigapanah, caused by drought which resulted in plants Karo people become corrupted. Dance tembut - tembut also has a function as a means of entertainment. Dance tembut - tembut been more dominant as a means of entertainment fun.In custom event ndilo wari this udan music acts include the like, Drum Five Sendalanen is comprised of: Sarune (fife, as carriers melody), drum Singindungi, (drum mother, as the carrier rhythmic variation), Singanai Drum (Drum children , as a carrier fixed rhythmic), Gung (Gong, as a determinant of the largest cycle, Penganak (Small Gong, as the smallest cycle carrier). Keywords: Tembut- tembut, Ndilo Wari ceremony Udan